Sowing speed in no tillage system on early development of maize crop - Paulo, Marcela Vieira; Tieppo, Rafael Cesar; Modolo, Alcir José; Dallacort, Rivanildo; Santi, Adalberto (Scientia Plena, 2018)
Sowing is a fundamental stage in crops’ cultivation process. If performed improperly, it can compromise the entire crop development. Seeding speed stands out as a key factor which can affect seeding quality. The objective of this study was to assess the effects of variation of working speed in maize initial establishment and in direct seeding’s’ quality parameters. The experiment was carried out in the municipality of Tangará da Serra – MT. Four seeding speeds were used V1 equal 1.11 (4.0), V2 equal 1.39 (5.0), V3 equal 1.67 (6.0) and V4 equal 1.94 m s-1 (7.0 km h-1). The assessed parameters were emergence speed index, emergence rate, seed deposition depth, plant spacing, and initial plant population. No interference of seeding speed variation was observed in seed deposition depth, emergence speed index and initial plant population. However, seeding speed influenced in plant spacing, in which speed increase was proportional to plant spacing increase.